PREVALENCE OF SLEEP DISORDERS IN PRIMARY HEALTH CARE CENTER, KARACHI, PAKISTAN (The Research of Medical Science Review, 2025)
Introduction: Sleep disorders are a growing concern worldwide, affecting individuals across various demographics. In Pakistan, limited research exists on the prevalence of sleep disorders in primary healthcare settings, particularly in urban areas like Karachi. Objectives: The study aimed to assess the prevalence of sleep disorders among the general population attending a primary healthcare center in Sikanderabad, Karachi, and identify associated demographic and lifestyle factors. Materials and Methods: A cross-sectional study was conducted using structured questionnaires, including the Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale, to assess sleep quality and daytime sleepiness. The sample consisted of 100 participants, including both male and female individuals from various socio-economic backgrounds. Results: 40% of participants reported poor sleep quality, with 55% experiencing excessive daytime sleepiness. Factors such as age, gender, income, and occupation were significantly associated with sleep disorders. Conclusion: Sleep disorders are prevalent in Karachi, particularly among certain demographics, highlighting the need for targeted interventions in primary healthcare.